Effect of different membrane use in micro-bacterical voltaic cell for electrical energy generation from wastewater - Selaman, Rafidah; Acho, Mohd Faizal; Nurdik, Mohd Ruzaleh; Lepit, Ajis (Universiti Teknologi MARA, Perak, 2025)
The sustainable, green and renewable energy are characteristics of energy source that are highly demanded nowadays. The world energy annual reported that the escalating electricity consumption will surpass energy output. For example, oil, biofuel, hydropower, nuclear and natural gas were projected depleted by 2050. Therefore, another alternative energy source from wastewater and design two columns of reactor was created, using the voltaic cell working principle that is capable to generate voltage. The voltage is one joule of energy per one coulomb unit charge passed. The wastewater contributed to the air pollution and released a bad smell to the surrounding environment. The method employed in this study was the anaerobic digestion (AD) from the fermentation process. Our aim in this study is to vary the type of membrane bridge in micro-bacterial cell, were parafilm, polyvinylidene fluoride-co-polyvinyllimdazole (PVDF-g-PVim) and agar-agar membranes, while the sample used was 100 mL of wastewater as a source for biocatalyst that was fixed with temperature of 35 oC fermentation. As a result, the value of voltage was increased from 0.50 V to 1.25 V measured using voltage meter, corresponding to parafilm membrane, agar-agar membrane and PVDF-g-PVim membrane, respectively. By optimizing the membrane bridge type, the voltage of the micro-bacterial cell was enhanced almost three times compared to a conventional membrane. Our findings suggested that the high voltage can be obtained by using a cheap and eco-friendly membrane, and yet the voltage production from micro-bacterial cell can be improved, thus providing another alternative energy source in the future.